Clinicodemographic profile of diabetic ketoacidosis and its management in hospitalized children – A prospective study - Vasudev, Kompally; Mothilal, Sabavat; Vijaykumar, Guduru (Indian Journal of Child Health, 2020)
Background: Diabetic ketoacidosis (DKA) is the leading cause of morbidity and mortality in children with Type 1 diabetes (T1DM). In developing countries, mortality is between 6 and 24%. Recent studies have documented that DKA in association with cerebral edema (CE) accounted for a mortality of 1–24% with a high rate of permanent neurologic morbidity. Objective: The objective of the study was to study the demographic profile, clinical presentation at the time of admission, management, and complications of patients diagnosed as T1DM with DKA. Materials and Methods: A prospective observational study was conducted among children admitted in PICU MGM hospital, Warangal, Telangana between December 2016 and November 2018. Children up to the age of 18 years diagnosed as T1DM who presented with DKA were included in the study. Sociodemographic profile, dietary intake, and treatment history of children were collected using a pre-designed pro forma. Clinical features and management were noted. Results: A total of 51 children were included in the study. Among them, 32 (62.74%) cases were newly diagnosed and 19 (37.2%) were previously diagnosed. A majority of the children belonged to lower socioeconomic status with 40% of the children suffering from severe grade of malnutrition. Classical symptoms of polyuria, polydipsia, and polyphagia were observed in 32 patients (62.74%). Vomiting was observed in 59% of cases, tachypnea in 82.35%, and abdominal pain in 29.41% of cases. About 54.90% of cases presented with severe and 33.3% with moderate DKA. Administration of regular insulin was the main modality of management in all cases. The major complication observed was hypoglycemia followed by cerebral edema. Conclusion: Cerebral edema with septic shock is a life-threatening complication of patients suffering with DKA. Active management with regular insulin can avert major complications and can lead to better outcomes.